Periphrasis: on the example of bilingual dictionaries - Nashirova , Shakhnoza Burievna (The Lingua Spectrum, 2026)
The presence of periphrases in bilingual dictionaries is in the focus of lexicographic research. It should be noted that the aspects that should be taken into account in the process of implementing the linguistic interpretation of periphrastic expressions are finding their equivalents in both languages, as well as filling the corresponding “lexical gap” in the absence of an alternative to the selected figurative expression in the second language, as well as preserving the features of emotional-expressive and stylistic coloring in the translation process. In general, the implementation of the linguistic analysis of periphrases in bilingual dictionaries creates an important basis for future research in this area.